A modelling framework for social media monitoring. (1st January 2013) - Semenov, Alexander; Veijalainen, Jari
This paper describes a hierarchical, three-level modelling framework for monitoring social media. Immediate social reality is modelled through the first level of the models. They represent various virtual communities at social media sites and adhere to the social world models of the sites, i.e., the 'site ontologies'. The second-level model is a temporal multirelational graph that captures the static and dynamic properties of the first-level models from the perspective of the monitoring site. The third-level model consists of a temporal relational database scheme that models the temporal multirelational graph within the database. The models are specified and instantiated at the monitoring site. An important contribution of the paper is the description of the mappings between the modelling levels and their schematic algorithmic implementation within the monitoring site. The paper also describes theoretical limits for the accuracy and timeliness of monitoring activity, assuming that the monitoring is performed remotely over the internet.